Climate indices of environmental change in the High Arctic: Study from Hornsund, SW Spitsbergen, 1979–2019 - Krzysztof Migała; Elżbieta Łepkowska; Marzena Osuch; Łukasz Stachnik; Tomasz Wawrzyniak; Dariusz Ignatiuk; Piotr Owczarek (Polish Polar Research, 2022)
An analysis of a suite of climatological indices was undertaken on the basis of long-term (1979–2019) climatological data from the Polish Polar Station in Hornsund, SW Spitsbergen. It was followed by an attempt to assess the scale of their impact on the local environment. The temperature and precipitation indices were based on percentiles of the variables calculated for a population of daily values from the climate normals for 1981–2010. A greater share of both cyclonic and anticyclonic circulations from the S and SW sectors, forcing the advection of warm air masses from the south, was decisive for the trends of change in comparison with the long-term mean. Both extreme precipitation and drought events depend on the 500 hPa geopotential height and precipitable water anomalies, determined by the baric field over the North Atlantic. Climate changes impact on the dynamics of local geoecosystems by causing faster glacier ablation and retreat, permafrost degradation, intensification of the hydrological cycle in glaciated and unglaciated catchments, and changes in the condition and growth of tundra vegetation.